Quantitative Structure-activity Relationship - Kandemirli, Fatma (IntechOpen, 2017)
The book, which is related to QSAR in sciences, is divided into five main chapters. The first chapter is the Introductory chapter. The second chapter aims to provide an update of the recent advances in the field of rational design of PDE inhibitors. The third chapter includes designing a series of peptidic inhibitors that possessed a substrate transition-state analog and evaluating the structure-activity relationship of the designed inhibitors, based on docking and scoring, using the docking simulation software Molecular Operating Environment. The aim of the forth chapter is to develop structure-property relationships for the qualitative and quantitative prediction of the reverse-phase liquid chromatographic retention times of chlorogenic acids. The final chapter aims to determine the model of interactions between the natural compounds with anti-inflammatory molecular target by molecular docking analysis.